Determinants and Dynamics of Schooling and Child Labor in Bolivia - Grigoli, Francesco; Sbrana, Giacomo (2012)
This paper investigates the determinants of primary school enrollment, attendance and child labor in Bolivia from 1999 to 2007. The analysis also aims at identifying the substitution and complementary relationships between schooling and working. Although enrollment rates show a significant improvement, lack of attendance remains an issue. The empirical results reveal that the increase in enrollment is led by indigenous children and those living in urban areas. Moreover, contrary to common belief, being extremely poor and indigenous are the main determinants of school attendance. Although extremely poor children increased their school attendance, they were not able to reduce child labor. However, for indigenous children school attendance and child labor were substitutes, increasing schooling and reducing child labor.